Kindling 6 - Corcoran, Michael E.; Corcoran, Michael E.; Moshé, Solomon L.; Moshé, Solomon L. (Advances in Behavioral Biology, 2005)
Kindling is the dominant animal model of epilepsy and the processes underlying the development of epilepsy. Studies of kindling have led to important insights into the mechanisms of epilepsy and potential treatments for seizures and seizure development. These proceedings of the Sixth International Conference on Kindling, held on June 2004 in Victoria, British Columbia, report the results of cutting-edge research on kindling and closely related phenomena. A broad array of themes concerned with research on epilepsy and kindling is covered in the book: Pathogenesis of kindling, including developmental patterns; electrophysiology; anatomy, morphology, and neural circuitry; genes, species, and strains; synaptic pharmacology and neurochemistry Behavioral consequences of kindling Drugs and interventions against kindling Clinical relevance of kindling for our understanding of epilepsy in patients About the Editors: Michael Corcoran is a Professor in the Department of Anatomy and Cell Biology at the College of Medicine at University of Saskatchewan, Saskatchewan, Canada. Solomon L. Moshe is Professor and Vice Chairman of Neurology, Albert Einstein College of Medicine, Bronx, New York.